1944
DOI: 10.1029/tr025i006p01005
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stream‐flow from alkalinity‐determinations

Abstract: Occasionally the engineer making stream‐measurements is required to obtain data at locations where conventional methods are of little value. Such was the problem of Madison Lakes Survey. This Survey has been charged with determining the pollution entering the lakes from the Nine Springs Sewage Treatment Plant, the Yahara River, and several small creeks (Fig. 1). Strength of pollution was determined by chemical analysis of samples which gave the strength of the sample in parts per million (ppm) or pounds per mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1944
1944
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The data for the Sr/Ca and Mg/Ca ratios for Mill Creek are presented in Figures 1 and 2, re- spectively. Lenz and Sawyer ( 1944) found that during extended dry periods alkalinity was a highly variable function of discharge. However, during periods of change or increased discharge, alkalinity decreased in proportion to the increase in discharge.…”
Section: Relationship Of Stream Discharge and Water Compositionmentioning
confidence: 99%
“…The data for the Sr/Ca and Mg/Ca ratios for Mill Creek are presented in Figures 1 and 2, re- spectively. Lenz and Sawyer ( 1944) found that during extended dry periods alkalinity was a highly variable function of discharge. However, during periods of change or increased discharge, alkalinity decreased in proportion to the increase in discharge.…”
Section: Relationship Of Stream Discharge and Water Compositionmentioning
confidence: 99%
“…Each pair yields a series of simulated concentrations (C sim ) that can be compared with the observed concentrations (C obs ). Among the many numerical criteria that could be used, we chose the bounded version of the Nash and Sutcliffe (1970) efficiency criterion NSEB (Mathevet et al, 2006), which is commonly used in hydrological modeling. NSEB can be computed on concentrations or on discharge-weighted concentrations (which corresponds to the load).…”
Section: Numerical Identification Of the Parameters For The 2s-aps Rementioning
confidence: 99%
“…The Nash and Sutcliffe (1970) efficiency (NSE) criterion is well known and widely used in the field of hydrology. The rescaling proposed by Mathevet et al (2006) transforms NSE into NSEB, which varies between −1 and 1 (its optimal value). The advantage of this rescaled version is to avoid the occurrence of large negative values (the original NSE criterion varies in the range [−∞, 1]).…”
Section: Numerical Identification Of the Parameters For The 2s-aps Rementioning
confidence: 99%
See 1 more Smart Citation
“…An alternative hypothesis is that higher solute con-centrations in Central Creek were due to lower runoff from its basin. This hypothesis is based upon the fact that concentration and discharge are inversely correlated within streams [e.g., Lenz and Sawyer, 1944;Durum, 1953;Steele, 1968;Cleaves et al, 1970;Keller, 1970;Edwards, 1973;lineson, 1973;Johnson and Swank, 1973;Walling, 1975;Zeman and Slaymaker, 1975;Feller, 1976]. This should extend to differences between basins, all other things being equal.…”
Section: Potassium Concentration In Firmentioning
confidence: 99%